TBC1D20 is Essential for Postnatal Uterine Development and Endometrial Decidualization in Mice - Wenpeng Min; Xi Li; Jing Zhou; Wei Yuan; Qing Yang; Xinmei Ji; Bing Liu; Liqiong Luo; Yuxia He; Lina Cui; Wen-Lin Chang (Clinical and Experimental Obstetrics & Gynecology)
Background: TBC1 domain family member 20 (TBC1D20) is important in male reproductive, eye lens function and neural system development. However, the role of TBC1D20 on reproduction in female mice remain unclear. Methods: As a prospective laboratory-based study, a mouse model with spontaneous functional mutations of Tbc1d20 (Tbc1d20-⁣/-) was employed to investigate the effect of Tbc1d20 on the fertility of female. Then the role of Tbc1d20 on postnatal female reproductive tract development and gonadal function was measured by immunohistochemistry assay and radioimmunoassay. A bilateral ovarian removal model and an artificial induced decidualization model were employed to reveal the function of Tbc1d20 on endometrial decidualization in vivo. Primary uterine stromal cells were isolated to evaluate the effect of Tbc1d20 on uterine stromal cell proliferation and the ability of decidualization in vitro. Results: Female Tbc1d20-⁣/- mice were infertile. Functional mutations of Tbc1d20 exerted no obvious changes on the function of ovary, structure of fallopian tubes, and ability of early embryo implantation. However, Tbc1d20-⁣/- mice presented marked reduction on the uterine size and weight at two-month-old, accompanied limitations on the myometrial thickness, the number of endometrial glands, and the density of blood vessels. Tbc1d20-⁣/- mice exhibited an impaired uterine decidualization phenotype in vivo. In addition, in vitro primary cell model indicated that the proliferation and differentiation of uterine stromal cells were retarded while Tbc1d20 loss of function. Mechanically, TBC1D20 deficiency triggered endoplasmic reticulum stress in proliferating and differentiating uterine stromal cells. Conclusions: The findings from this study indicated that TBC1D20 is necessary for normal postnatal uterine development and endometrial decidualization in mice.